The Anti-osteoporotic Effect of Avena sativa Seeds Ethanolic Extract on Methylprednisolone -induced Osteoporosis in Female Rabbits (Lepus cuniculus) - Mariam abdulhussain kadhem; Falah musa AL-Rekabi (مجلة الانبار للعلوم البيطرية)
Glucocorticoids are one of the causes of secondary hyperthyroidism lead to osteoporosis. The experiment was conducted to investigate the role of Avena sativa L. (oat) seeds ethanolic extract on osteoporosis in female rabbits treated with methylprednisolone, by studying the BMD, serum Ca and P, Vit. D, PTH, and histopathological alterations of femur bone. Fifty female rabbits were used, weighted 1500- 2000gm and aged 8 month, were divided into five equal groups, each group contains ten adult female rabbits. Control negative group(G-ve ), 2. Control positive group(G+ve) (Meth-Pred) received S/C methylprednisolone of 0.2 mg/kg per day for 30 days then received orally 1ml/kg normal saline per day for two months, 3. Group3 (Meth-Pred+As) received similar dose of Meth-Pred then treated with 600 mg/kg Avena sativa seed extract orally per day for two months, 4.Group4(Meth-Pred+Alend) received similar dose of Meth-Pred then treated by alendronate 3.6 mg/kg BW orally weekly for two months, 5. Group5 (Meth-Pred+ Alend + As) received similar doses of Meth-Pred then treated by Alend then treated with Avena sativa seed extract. This study persisted for three month and till after one week of the medicine’s withdrawal. The results showed that the BMD, serum Ca, phosphorus, Vit. D, a significantly declined (p≤ 0.05), as well as a significantly high ( P≤0.05) in serum PTH of the animals after two month of treatment, and after one week of withdrawal of treatment in control(+ve) and alendronate group compared with control(-ve), but when treated rabbits with Avena sativa ethanolic extract in third group, showed an improvement in the parameters above return to its normal values and produced excellent results. Histopathological alterations of the femoral bone of control (+ve) group including abnormal histological appearance of the bone. Whereas treated with Avena Sativa seeds ethanolic extract in third group were effective in arresting histopathological alterations and normal architecture compared with the control (-ve) group. These finding suggest that the ethanolic extract of Avena Sativa seeds may be an effective therapeutic agent for the treatment and prevention of osteoporotic bone loss